2014
DOI: 10.1007/s11914-014-0209-0
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Crosstalk Between Muscle and Bone

Abstract: The musculoskeletal system is a complex organ comprised of the skeletal bones, skeletal muscles, tendons, ligaments, cartilage, joints, and other connective tissue that physically and mechanically interact to provide animals and humans with the essential ability of locomotion. This mechanical interaction is undoubtedly essential for much of the diverse shape and forms observed in vertebrates and even in invertebrates with rudimentary musculoskeletal systems such as fish. It makes sense from a historical point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 92 publications
1
74
0
Order By: Relevance
“…A growing amount of data suggests that muscle and bone can signal in a paracrine and endocrine fashion through secreted factors such as myokines and osteokines (for review [35]). Myostatin is a growth factor produced primarily by muscle, secreted into the circulation, and is a candidate for bone-muscle crosstalk as it has been shown to decrease osteogenic differentiation of bone marrow-derived mesenchymal stem cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…A growing amount of data suggests that muscle and bone can signal in a paracrine and endocrine fashion through secreted factors such as myokines and osteokines (for review [35]). Myostatin is a growth factor produced primarily by muscle, secreted into the circulation, and is a candidate for bone-muscle crosstalk as it has been shown to decrease osteogenic differentiation of bone marrow-derived mesenchymal stem cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Other work 4 has shown that the relative content and half-life of this 18-kDa fragment in bone cells is increased after treatment with AEBSF, which blocks autolytic cleavage of MBTPS1. Consistent with cre recombinase-mediated deletion of Mbtps1, the 18-kDa MBTPS1 band is barely detectable in two of three Mbtps1 cKO bone extracts and noticeably reduced in a third specimen (Fig.…”
Section: Mbtps1 Mrna and Protein Are Deleted In Osteocyte-enriched Bomentioning
confidence: 86%
“…Osteoid osteocytes control bone mineralization by secretion of DMP1, phosphate-regulating endopeptidase homolog, X-linked (PHEX), and matrix extracellular phosphoglycoprotein (MEPE) (1), whereas mature osteocytes secrete sclerostin, an inhibitor of bone formation, and regulate phosphate homeostasis and, indirectly, bone mineralization via production of FGF23 (2). Osteocytes are the mechanosensory cells in bone and appear to regulate muscle function and myogenesis (3)(4)(5). Specifically, deletion of connexin43 in osteoblasts/osteocytes shows it is involved in postnatal bone-muscle cross-talk via an osteocalcin-mediated stimulation of muscle formation and function (5).…”
mentioning
confidence: 99%
“…Decreased muscle function caused by physical inactivity or aging is strongly correlated with decreased bone mass and morphology 36,37) . Therefore, it has been suggested that the crosstalk between muscle and bone is mediated via mechanical stimuli and cytokines 38,39) . It is also empirically known that the interactions between muscle and bone are important during the bone repair following a fracture.…”
Section: Crosstalk Between Satellite Cells and Other Organsmentioning
confidence: 99%